Rear-surface line-contact optimization using screen-print techniques on crystalline solar cells for industrial applications. (15th August 2018) - Ho, Jiajer; Wu, Te-Chun; Ho, Jyh-Jier; Hung, Chih-Hsiang; Chen, Sung-Yu; Ho, Jia-Show; Tsai, Song-Yeu; Chou, Chau-Chang; Yeh, Chi-Hsiao
Abstract: This paper explores the utility of single-crystalline silicon solar cells that are treated with the screen-print technique to implement line contacts at the cells' rear surfaces. We designed rear-surface line-contact (RSLC) solar cells using screen-print methods on n -type wafers (125 ×125 mm 2 ) in order to produce rear surface passivation layers. The performances of these cells were then evaluated and compared to laser fired contact solar cells. We examined the rear surface passivation quality of a stack consisting of an aluminum oxide (Al2 O3 ) passivation layer deposited by atomic layer deposition, overlaid with a silicon nitride (Si3 N4 ) layer deposited by plasma-enhanced chemical vapor deposition. The initial outstanding surface passivation quality provided by the Al2 O3 /Si3 N4 stacks remained high after annealing, as indicated by the average light-beam-induced-current value (85.1 mA/cm 2 ) for the developed RSLC cells. RSLC cells exhibited conversion efficiencies of up to the optimal 18.48%, demonstrating that line-contacting processes were consistent with print screen and that the simplification of electrode process may be realized for industrial applications.